2023
DOI: 10.3390/membranes13050458
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Circular Bioeconomy: Exploring Pineapple Stem Starch Film as a Plastic Substitute in Single Use Applications

Abstract: In this study, biodegradable starch film was developed from pineapple stem waste as a substitute for non-biodegradable petroleum-based films for single-use applications where strength is not too demanding. High amylose starch from a pineapple stem was used as the matrix. Glycerol and citric acid were used as additives to adjust the ductility of the material. Glycerol content was fixed at 25% while that of citric acid varied from 0 to 15% by weight of starch. Films with a wide range of mechanical properties can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
2
5
2
Order By: Relevance
“…The crystalline structure is different from that of the original PSS, which has an A-type structure, similar to other types of starches as shown previously [ 27 ]. The appearance is similar to that of PSS film prepared by solution casting [ 29 ] and that of ozonated cassava starch films [ 11 ]. These crystalline peaks are attributed to the spontaneous recrystallization of amylose molecules during film drying [ 43 , 44 ] or retrogradation.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The crystalline structure is different from that of the original PSS, which has an A-type structure, similar to other types of starches as shown previously [ 27 ]. The appearance is similar to that of PSS film prepared by solution casting [ 29 ] and that of ozonated cassava starch films [ 11 ]. These crystalline peaks are attributed to the spontaneous recrystallization of amylose molecules during film drying [ 43 , 44 ] or retrogradation.…”
Section: Resultssupporting
confidence: 60%
“…This is because the PSS has a relatively high amylose content and can be obtained from pineapple field waste, which is abundantly available in Thailand [ 26 , 27 , 28 ]. We reported that the PSS film exhibits good properties, such as high water resistance, low water absorption, and good mechanical strength, while still being readily biodegradable [ 29 ]. As a result, the PSS film has been proposed for use in single-use or disposable applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thermosetting plastic (9% to 21% water solubility) showed a higher water resistance than thermoplastic starch obtained from unmodified pineapple stem starch (32% to 37% water solubility). This research revealed the higher efficacy of thermosetting pineapple stem starch materials for water-resistant ability compared to pineapple stem starch-based plastic reported by Namphonsane et al [ 32 ] and Thongphang et al [ 33 ], which revealed a water resistance of (17 to 25)% and (15 to 32)%, respectively, depending on glycerol content. Furthermore, the thermosetting starch displayed a slowed biodegradation rate while still retaining biodegradability.…”
Section: Discussionmentioning
confidence: 55%
“…Our previous work has revealed that PSS stands out as a distinctive starch type with elevated amylose content in comparison to other variants [ 31 ]. Moreover, films derived from PSS exhibit robust mechanical strength and exceptional water resistance, while retaining biodegradability [ 32 ]. The versatility of PSS-based materials has been explored in the creation of composite sheets [ 33 ], protective coatings for fruits and vegetables [ 34 ], rigid foam [ 35 ], water-based adhesives [ 36 ], food applications [ 37 , 38 ], and more.…”
Section: Introductionmentioning
confidence: 99%
“…The water-resistant ability of the PLA blend samples was assessed in terms of water absorption, following the modified approach reported previously by Namphonsane et al [ 39 ]. The sample sheets with a dimension of 20 mm × 20 mm (width × length) were dried in a hot-air oven at 80 °C for 24 h to remove the humidity in the samples and the dried weight was recorded, which was defined as w i .…”
Section: Methodsmentioning
confidence: 99%